Female Patenting Activity in Mexico: Understanding the Gender Gap - Sifontes, Domingo (2022)
The study of patenting activity may help to understand the existing gender differences in the field of science and technology. This research analyzes how organizational issues have  an  effect  on  female  presence  in  Mexico  patenting  activity  for  the  period  1976-2017.  To  that  end,  this  investigation  studies  patents  granted  to  Mexico  by  the  United  States Patent Office (USPTO). The results show that teamwork and the way in which the patenting  process  is  organized  are  important  to  explain  female  presence  in  patenting  activities, and that organizations such as universities and laboratories are also linked to a greater probability of female presence in patenting.